Oral or Topical Pain Therapy—How Would Patients Decide? A Discrete Choice Experiment in Patients with Peripheral Neuropathic Pain. Issue 5 (1st February 2021) - Schubert, Tino; Kern, Kai‐Uwe; Schneider, Sabine; Baron, Ralf
Abstract: To ensure an adequate pain therapy with high patient adherence, it is necessary to know and consider patient preferences. A discrete choice experiment was used to obtain patients' preferences regarding treatment with systemic or topical pain medication. Patients with peripheral neuropathic pain (pNP) were recruited in two pain‐focused practices in Germany. To identify relevant attributes of topical or systemic pain medication, a literature review and face‐to‐face interviews with experts for pain treatment were conducted. The attributes used in the choice scenarios were noticeable onset of effect, time spent in medical office, risk of systemic and local side effects, and impairment of daily life with regard to sleep quality and sexuality. The model was estimated with a mixed multinomial logit regression model. The study included 153 participants suffering from moderate to severe pNP. Most important attributes from patient's perspective was noticeable onset of effect (odds ratio 2.141 [95% confidence interval 1.837 to 2.494]), followed by risk of systemic side effects (2.038 [1.731 to 2.400]) and risk of sexual dysfunction (1.839 [1.580 to 2.140]), while risk of local side effects regarding skin ranked fourth (1.612 [1.321 to 1.966]). The impairment of sleep quality was also significant but less important (1.556 [1.346 to 1.798]). Local side effects were more likely to be accepted than systemic side effects. The risk of sexual dysfunction as a side effect of treatment is very important for patients, although it has received little attention in the literature.